To solve the factored quadratic equation \( 0 = -\frac{1}{3}x(x - 6) \), we can set each factor equal to zero.
-
Start by rewriting the equation: \[ -\frac{1}{3}x(x - 6) = 0 \]
-
Since the product is equal to zero, we can set each factor to zero:
-
The first factor: \[ -\frac{1}{3}x = 0 \] Multiplying both sides by -3 gives: \[ x = 0 \]
-
The second factor: \[ x - 6 = 0 \] Adding 6 to both sides gives: \[ x = 6 \]
-
-
Therefore, the solutions to the equation are: \[ x = 0 \quad \text{and} \quad x = 6 \]
The solutions to the factored quadratic equation are \( x = 0 \) and \( x = 6 \).